2D spatially resolved O atom density profiles in an atmospheric pressure plasma jet: from the active plasma volume to the effluent. (22nd June 2021) - Steuer, David; Korolov, Ihor; Chur, Sascha; Schulze, Julian; Schulz-von der Gathen, Volker; Golda, Judith; Böke, Marc
Abstract: Two-dimensional spatially resolved absolute atomic oxygen densities are measured within an atmospheric pressure micro plasma jet and in its effluent. The plasma is operated in helium with an admixture of 0.5% of oxygen at 13.56 MHz and with a power of 1 W. Absolute atomic oxygen densities are obtained using two photon absorption laser induced fluorescence spectroscopy. The results are interpreted based on measurements of the electron dynamics by phase resolved optical emission spectroscopy in combination with a simple model that balances the production of atomic oxygen with its losses due to chemical reactions and diffusion. Within the discharge, the atomic oxygen density builds up with a rise time of 600 µ s along the gas flow and reaches a plateau of 8 × 10 15  cm −3 . In the effluent, the density decays exponentially with a decay time of 180 µ s (corresponding to a decay length of 3 mm at a gas flow of 1.0 slm). It is found that both, the species formation behavior and the maximum distance between the jet nozzle and substrates for possible oxygen treatments of surfaces can be controlled by adjusting the gas flow.